Strategi Group Investigation dalam Pembelajaran Mahārat al-Qirā’ah pada Mahasiswa Jurusan Bahasa dan Sastra Arab, UIN Maulana Malik Ibrahim, Malang - Amalia H. Islamiyah; Muassomah (Al-Ma‘rifah, 2020)
In learning reading skills (mahārat al-qirā’ah), especially Arabic texts, students are required to be able to reach existing indicators, which are at the level of critical reading. One effort to foster a critical attitude is to implement a group investigation strategy in the learning process. Therefore, the purpose of this study is to see how far the effectiveness of applying the group investigation strategy in learning mahārat al-qirā’ah 2 to the students of Arabic Language and Literature Department, UIN Maulana Malik Ibrahim. The results of this study prove that the application of the group investigation strategy applied in learning mahārat al-qirā’ah 2 can make students active and critical in analyzing discourse. The obstacle is the lack of student commitment to time so that the learning seems rushed. The solution, students are accustomed to reading Arabic texts so that they are familiar with new mufradāt (vocabulary), and commitment to the time given by lecturers so that learning is more effective and efficient.